Spatiotemporal evolution of venous narrowing in acute MS lesions - Eisele, Philipp; Szabo, Kristina; Ebert, Anne; Platten, Michael; Gass, Achim (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2018)
Objective To investigate the spatiotemporal evolution of venous narrowing in newly developing MS lesions in a longitudinal MRI study including susceptibility-weighted images (SWIs). - Methods We retrospectively investigated serial MR examinations of 18 patients with MS acquired on a 3T MRI system including SWI for acute contrast-enhancing lesions with at least 1 MRI examination before contrast enhancement. The mean diameter of veins at the time point of contrast enhancement was compared with the mean diameter of veins before and after contrast enhancement. - Results A total of 40 acute contrast-enhancing lesions with a corresponding intralesional central vein were included in the study. The mean diameter of intralesional veins at the time of contrast enhancement (0.80 ± 0.12 mm) was smaller than that at before (1.16 ± 0.19 mm) and after contrast enhancement (1.07 ± 0.15 mm; p < 0.001 for all comparisons). - Conclusions Our ﬁndings contribute to the increasing database of plaque development and evolution. The smaller diameter of intralesional veins on SWI at the time of blood-brain barrier breakdown may reﬂect morphologic changes because of perivascular inﬂammation and/or decreased levels of deoxygenated hemoglobin.
Gesehen am 08.08.2019